(untitled) (Swiss Medical Weekly, 2020)
BACKGROUND In 2018, Switzerland introduced a nationwide case-based prospective remuneration system (TARPSY), with decreasing daily rates for reimbursement of inpatient care in mental health facilities. Initially, there were concerns that declining daily rates could result in early discharges and increased readmission rates. METHODS We compared length of stay (LOS) and readmission rates for patients in adult and geriatric psychiatry treatment at four psychiatric hospitals between 2017 (the last year with the traditional remuneration system) and 2018 (the first year with TARPSY). RESULTS A total of 26,324 treatment episodes of 15,464 patients were analysed. The reduction of average LOS was not statistically significant in the first year after the implementation of TARPSY, neither in adult (mean –0.6 days, 95% confidence interval [CI] –1.6 to 0.4; p = 0.226) nor in geriatric psychiatry (mean −1.6 days, 95% CI −3.8 to 0.7; p = 0.178). When compared with the traditional remuneration system with fixed daily rates, the readmission risk was statistically significantly reduced by −9.1% (95% CI −4.9 to −13.1%; p <0.001) in adult psychiatry but not in geriatric psychiatry (−6.8%, 95% CI −19.2 to 7.4%; p = 0.329). CONCLUSIONS If being evident at all, the effects of the new remuneration system TARPSY on LOS and readmission rates seem to be small. Concerns that declining daily rates in TARPSY would result in early discharges and increased readmission rates did not prove true in adult and geriatric psychiatry.